Hunger and malnutrition in the countries of the Association of Caribbean States (ACS) - Martínez, Rodrigo (CEPAL SantiagoCL, 2005)
Describes the characteristics of extreme poverty, food security, malnutrition and micronutrient deficiencies, with a look at the prospects of fulfilling the Millennium Development Goals. Identifies vulnerable groups and the economic effects associated with malnutrition. Describes the main policies and programmes under implementation together with proposals aimed at maximizing the cost effectiveness of such interventions.